Long-COVID and its Physical and Neurological Symptoms in Adults: A Systematic Review - Abdul Mannan Baig, Sameera Rizvi, Shahla Pardhan, Joachim Gerlach, Tazeen Saeed Ali (Pakistan Journal of Medical & Health Sciences, 2023)
This review was carried out with the objective to study patterns of neurological, psychological and other physical consequences of COVID-19 in the long term. The guidelines of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) had been followed; 22 articles, published during January 2020 to September 2021, were selected. Original research, review articles, editorial and viewpoints were included. Google Scholar, Medline, and PubMed were searched through 2020 till 2021.Data collection in selected studies was performed mainly through the online survey, telephone survey, use of medical records, and patient interviews. This systematic review contains the studies conducted in the American, Asian and European countries. The major outcomes identified were the neurological, psychological, and other long-term chronic manifestations of COVID‐19. This review demonstrates that long-COVID has started to bring a huge wave of patients, the count of them being millions now, who can enter a phase of disability due to neurological damages if not treated during the early course of illness. Though more disabling than lethal, long-COVID patients with a neurological deficit is expected to overburden the healthcare system globally which is already been struggling to handle acute COVID-19 patients in this once-in-a-lifetime pandemic. Keywords: COVID-19, Neurological and Psychological symptoms, Physical Symptoms, Long-COVID.